Оптимізація технологічних систем глушіння свердловин в умовах низьких пластових тисків - Bodachevskaia L.Yu.; Pop G.S.; Beiko I.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
On the basis of test data the method of multicriterion optimization of environmentally safe compositions of the technological systems of killing of well under low reservoir pressure has been developed. The created mathematical model of optimization allows to carry out the operative search of optimum decisions at any changes of composition and number of components for achievement of defined properties in the desired varying scopes.